Effect of liquid lipid on citrus aurantifolia oil loaded structured lipid carrier [electronic resource] - 279971 Abu Zarl Mohd. Mahfuz (2009)
Project Paper (Sarjana Muda Kejuruteraan (Kimia)) - Universiti Teknologi Malaysia, 2009